(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article discusses the features of the idea of human dominance over nature, proclaimed in a fairly obvious form in the Bible. Later, as the Christian civilization developed, the Europeans spread the Christian ecological paradigm. At present, mankind largely continues to adhere to this paradigm.